A conversão da “Besta”: apocalipse e escatologia no pensamento de René Girard - Righi, Maurício Gonçalves (2018)
This thesis can be summarized as a thorough study in mimetic theory, highlighting its internal and gradual development towards apocalypse, here understood as a current of thought. Making extensive use of Rene Girard’s (the founder of mimetic theory) books and thought, this work sustains a progressive shift in the categories and anthropological concepts of the mimetic theory towards the categories and theological concepts of the apocalypse, which marked a major resignification in Girard’s last works. Having this internal development as our background, this work is also meant to problematize some critical questions about modernity, especially its masked violence, nevertheless, very real and daily present in our world, and it does so to meet some central postulates in mimetic theory and apocalypse. In this internal dialogue between different lines of thought, between the modern and the archaic, between theology and anthropology, we propose a new investigation line for religious studies, in which we can raise some questions about the universality of the religious and religion in human culture and mind, observing its integrating role and even founding one in the institutional and moral realms. We have, therefore, a work in religious studies that reinstates some of the religious anthropology most cherished themes, reinterpreting them in the light of mimetic theory and apocalypse